Pemanfaatan Komputer Tablet Android Sebagai Pengendali Robot Beroda Empat - Arie S. M. Lumenta (Universitas Sam Ratulangi, 2012)
Android is open source so that developers can do with application and modify freely. The growing interest in mobile software developers to create software that can be useful human needs. Robotics technology in the world today is rapidly growing and changing as more and more advanced robot control system. Interfacing to control robot itself can be a problem while the use of cables for control is seen as less effective and efficient. This research aims to create tablet pc applications as android based robot controller by using wireless LAN and make the android as multifunctional mobile devices, as well as communicaton tool but also as a device that is commicated to control hardware device. Based of results of tests performed, the system can work well in accordance with the purpose of the developer. Applications are made to run various types of android operating system with a screen resolution and hardware that different of android device. Data communication with a mobile robot as well, the data sent by the robot motion can be processed in realtime with a transfer time <1 second on the condition of different signals. Range of application of the control system can be control depending on the specification of wireless robotic device that is used both in the receiver and sender. Keyword : Android, developer software mobile, interfacing, wireless LAN, Robot